Intelligence and event-related potentials in a backward-masked auditory discrimination task: Analysis of speed and stages of information processing. - Bazana, P. Gordon. (University of Ottawa (Canada), 2001)
The relation between speed of auditory discrimination and intelligence was investigated. Thirty-six females in experiment 1 and 24 in experiment 2 completed the Multidimensional Aptitude Battery (MAB; Jackson, 1984). Subjects were divided into higher (HA) and lower (LA) ability groups. An auditory oddball paradigm was employed, with the addition of a masking stimulus (1000 Hz, 55ms duration) following the standard (600 Hz, 25 ms) and deviant (700 Hz, 25 ms) tones. The interval between standard or deviant offset and masking tone onset, the stimulus onset asynchrony (SOA), was varied at 150, 50 and 25 ms. The auditory discrimination task was presented in a passive condition in which participants ignored the tones while reading a book and in an active condition wherein they detected the deviant tone. The passive condition generated the mismatch negativity (MMN), an event-related potential measure that indexes the operation of echoic memory. The active condition produced behavioural data and P3, an ERP measure associated with stimulus evaluation and classification. In both experiments, HA participants detected more deviant tones, and had faster and less variable reaction times. Overall, P3 amplitude was significantly larger for HA subjects, with some differences in P3 latency observed. The HA group bad larger MMN amplitude in the first study only; shorter MMN latencies for the HA group were observed in study 2 only. An intensity manipulation in experiment 2, intended to manipulate task difficulty, produced no graded changes in any of the variables. Results for both experiments were combined to increase power and facilitate interpretation. Overall, results indicate that more intelligent individuals process information in short-term memory more rapidly than those of lower-ability; results also suggest that speed of processing in echoic memory may underlie ability-related differences in performance.
Keywords: Psychology, Cognitive.